Efficacy and safety of liver support devices in acute and hyperacute liver failure: a systematic review and network meta-analysis - Anna Kanjo (Nature Portfolio, 2021)
Abstract Acute liver failure (ALF) is a potentially life-threatening condition. Liver support therapies can be applied as a bridging-to-transplantation or bridging-to-recovery; however, results of clinical trials are controversial. Our aim was to compare liver support systems in acute and hyperacute liver failure with network meta-analysis. After systematic search, randomized controlled trials (RCT) comparing liver support therapies in adults with acute or hyperacute liver failure were included. In-hospital mortality was the primary outcome, the secondary outcomes were hepatic encephalopathy and mortality-by-aetiology. A Bayesian-method was used to perform network meta-analysis and calculate surface under the cumulative ranking curve (SUCRA) values to rank interventions. Eleven RCTs were included. BioLogic-DT and molecular adsorbent recirculating system (MARS) resulted in the lowest mortality (SUCRAs: 76% and 73%, respectively). In non-paracetamol-poisoned patients, BioLogic-DT, charcoal hemoperfusion and MARS may be equally efficient regarding mortality (SUCRAs: 53%, 52% and 52%, respectively). Considering hepatic encephalopathy, extracorporeal liver assist device (ELAD) may be the most effective option (SUCRA: 78%). However, in pairwise meta-analysis, there were no statistically significant differences between the interventions in the outcomes. In conclusion, MARS therapy seems to be the best available option in reducing mortality. Further research is needed on currently available and new therapeutic modalities. (CRD42020160133).